Some thoughts on racial-ethnic groups' representation in America: comments on the dimensions, issues, and dilemmas. (3rd July 2017) - Hero, Rodney
ABSTRACT: This essay presents an overview of an array of various conceptual, empirical, and normative issues regarding "representation" in the U.S. political system, particularly emphasizing racial/ethnic groups and representation. I consider some major questions which have been addressed, how they have been framed and examined, and findings on some of the numerous dimensions and sub-dimensions in political science research on questions, theories, and analyses of representation in several arenas of the political system. As such, the essay will engage several broad concerns which animate intellectual concerns and aspirations which are part of past and contemporary public discourse. I provide only limited original research, however, largely because trying to place some of the issues and research in broader context is as (or more) important at this juncture of American politics and political science inquiry. Complex and difficult issues of gender, race/ethnicity, and related matters regarding authenticity, identity, equality, and representation underscore these points.